LEARNING DELIVERY AND COMMITMENT, PERCEIVED MOTOR COMPETENCE, AND ANXIETY WHEN MAKING MISTAKES OR UNDER STRESS: MOTIVATING FACTORS IN ADOLESCENTS FOR ACHIEVEMENT DURING PHYSICAL EDUCATION CLASSES - Márquez-Barquero, Magally (2018)
Objective: to determine the factors associated to motivation in students for achievement of III cycle (seventh, eighth, and ninth grades) of the General Basic Education during Physical Education classes. Methodology: The AMPET questionnaire (Achievement Motivation in Physical Education Test) was applied to a total of 396 students (178 women and 218 men) of high school from five public educational centers, located in the Central Canton of the Province of Heredia, Costa Rica. A descriptive analysis was made with averages and standard deviations, 2x3 factorial ANOVA for independent groups. Results: Differences (p = .000) were observed in the commitment factor and learning delivery according to the academic level. When doing a post-hoc Tukey, it was found that the lower the academic level, the greater the commitment and learning delivery; that is to say, the seventh grade students reflect a higher score in the factor of commitment and learning delivery (4.03 ± .06) in comparison with eighth level (3.60 ± .05) and ninth level students (3.62 ± .06). With respect to the perceived motor competence factor, differences were obtained (p = .000) according to sex. The above reflects that men have a greater perceived motor competence (3.03 ± .06), compared to women (2.62 ± .07). Regarding the anxiety factor when making mistakes or under stress situations, statistically significant differences were found (p = .000); according to sex, women obtained a higher score in anxiety when making mistakes or under stress situations 2.51 ± .06), compared to men (2.16 ± .05). Conclusion: The research revealed that women respond differently than men to the factors associated with achievement motivation and it should be noted that physical education is a source of stress for them, an important fact to analyze to know its cause, and whether it is due to the existence of a gap in motor competence that has consequences on behavior, as well as to compare whether this behavior is repeated in schools in different regions of the country.